A Comparative Study of the Prameters in the Industrial Effluent in Trichy Region - Sekar, K.G.; Rajaji, R. (Asian Journal of Chemistry, 2010)
For many years, many industries like chemical industries, refineries etc. employed various chemical treatments along with water. After processing, the effluents are discharged. The influence of these effluents on human health has been undertaken on a large scale in our country and are controlled by environment bodies. Six different water samples of Trichy region were analysed. This work includes all aspects of the treatment of effluents arising from various branches of various industries. In sympathy with modern legislative trends, the emphasis is one means of avoiding or at least minimising the pollutants present in the effluent. The results obtained and discussed herein suggest that water from various industries which contains relatively low hardness (total, temporary and premanent hardness) and low pH values with acceptable limits. The present study has been done to compare the parameters for combined, treated effluents in winter and rainy season and biodegradability in winter season.